Prognostic value of integrated cardiopulmonary ultrasound in inpatients with acute heart failure with preserved and reduced ejection fraction and without heart failure. (25th November 2020) - Pugliese, N.R; Frassi, F; Frumento, P; Poggianti, E; Mazzola, M; De Biase, N; Landi, P; Masi, S; Taddei, S; Pang, P; Sicari, R; Gargani, L
Abstract: Objective: To assess the prognostic value of B-lines integrated with echocardiography in patients admitted to a Cardiology Department, with and without acute heart failure (AHF). Background: Lung-ultrasound (LUS) B-lines are sonographic signs of pulmonary congestion and can be used in the differential diagnosis of dyspnea to rule in or rule out AHF. Their prognostic value at admission is less established, as well as the different role in AHF with reduced and preserved ejection fraction (HFrEF and HFpEF), or patients admitted for cardiac conditions but without overt signs and symptoms of AHF. Methods: A total of 1021 consecutive in-patients (69±12 years) admitted for various cardiac conditions were enrolled. Patients were classified into three groups: 1) acute HFrEF; 2) acute HFpEF; 3) no AHF. All patients underwent on the admission an echocardiogram coupled with LUS, according to standardised protocols. Results: Patients were followed-up for a median of 14.4 months (interquartile range: 4.6–24.3) for death and HF readmission (composite endpoint). During the follow-up, 126 events occurred. Kaplan-Meier survival analyses showed admission B-lines >30 identified patients with worse outcome at follow-up in the overall population and each of the three groups (Figure). At multivariable analysis (Table), admission B-lines >30, EF <50%, tricuspid regurgitation velocity >2.8 m/s and tricuspid annular plane systolic excursion (TAPSE) <17 mm resulted in independent predictors of the composite endpoint. B-lines >30 had a strong predictive value in HFpEF and non-AHF, but not in HFrEF. Conclusions: Ultrasound B-lines can detect subclinical pulmonary interstitial edema in patients thought to be free of congestion, and provide useful information not only for the diagnosis but also for the prognosis in different cardiac conditions. Their added prognostic value among standard echocardiographic parameters is stronger in patients with HFpEF compared to HFrEF. Funding Acknowledgement: Type of funding source: None